2021
DOI: 10.12973/eu-jer.10.1.327
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Shared Leadership, Employee Empowerment and Innovativeness in Primary Schools: A Structural Equation Modeling

Abstract: Shared leadership and employee empowerment develop positive feelings in employees towards the organization, the work they do and themselves. These positive emotions create confidence for employees to try new methods and techniques in their work. Employees who approach their work with an innovative mindset will be more beneficial to their organizations and increase their own satisfaction. In this study, the shared leadership, employee empowerment and innovativeness levels of schools, the relationship of these v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The supervision factor becomes urgent because teachers can get support from other co-workers to increase the chances of successful ideas (Mishra et al, 2019;Toropova et al, 2021). Supervision led by the principal is also proven to have a significant relationship with the implementation of teacher empowerment so that teachers are increasingly motivated to create innovations (Cobanoglu, 2021). Unfortunately, other studies' findings refute this study's results, in which teachers perceived supervision in learning as typical (Chapagain, 2021;Yucel & Minnotte, 2017).…”
Section: Discussionmentioning
confidence: 55%
“…The supervision factor becomes urgent because teachers can get support from other co-workers to increase the chances of successful ideas (Mishra et al, 2019;Toropova et al, 2021). Supervision led by the principal is also proven to have a significant relationship with the implementation of teacher empowerment so that teachers are increasingly motivated to create innovations (Cobanoglu, 2021). Unfortunately, other studies' findings refute this study's results, in which teachers perceived supervision in learning as typical (Chapagain, 2021;Yucel & Minnotte, 2017).…”
Section: Discussionmentioning
confidence: 55%
“…For example, Fransen et al (2020) found that shared leadership positively fostered a sense of autonomy, competence, and impact. Similarly, Cobanoglu (2021) demonstrated that shared leadership behaviours, such as delegating authority and encouraging participation, were positively associated with employees' perceptions of empowerment.…”
Section: The Role Of Psychological Empowerment (Pe)mentioning
confidence: 95%
“…A large number of authors (He et al, 2020;Hoch 2013;Sun et al 2016;Klasmeier & Rowold 2020;Cobanoglu 2021) talk about the high impact of shared leadership on creativity and innovation. This seems to be a very frequent topic, however, the articles view creativity as a process of generating creative solutions and implementing innovations rather than as a skill or competence of individuals and teams.…”
Section: Other Findingsmentioning
confidence: 99%